FAKTOR YANG MEMPENGARUHI KELELAHAN DAN KECEMASAN PADA IBU PRIMIPARA PASCAPERSALINAN - Dahlia Murni; Sandra Harianis; Nurul Indah Sari; Dewi Erlina Asrita Sari (STIKES HUSADA GEMILANG, 2025)
The postpartum period is a critical phase for mothers after childbirth, where postpartum fatigue is a common issue that can affect both physical and mental health. This fatigue is influenced by internal factors such as hormonal changes and lack of rest, as well as external factors like social support and maternal anxiety levels. This study is a Quasi-Experimental research with a Nonequivalent Time Sample Design, conducted from September to November 2024 at Gajah Mada Tembilahan Public Health Center. The respondents in this study were postpartum mothers within the working area of Gajah Mada Tembilahan Public Health Center. The sampling method used was systematic random sampling, with a total of 15 respondents. The research instrument was a questionnaire designed to assess maternal anxiety and postpartum fatigue levels. The study results showed that most respondents experiencing fatigue were aged between 28-35 years, had a high school education as their last level of education, and received primary support from their husbands. A significant proportion of mothers (67%) experienced severe fatigue, influenced by perineal pain, back pain, and prolonged labor. Additionally, more than half of the respondents (53.3%) experienced high anxiety levels. Masa nifas adalah periode kritis bagi ibu setelah melahirkan, di mana kelelahan postpartum menjadi masalah umum yang dapat berdampak pada kesehatan fisik dan mental ibu. dipengaruhi oleh faktor internal seperti perubahan hormonal dan kurangnya istirahat, serta faktor eksternal seperti dukungan sosial dan tingkat kecemasan ibu Penelitian ini adalah penelitian Quasy-Experimental design dengan rancangan Nonequivalent time sample design penelitian dilakukan pada bulan September – November 2024 responden dalam penelitian ini yaitu ibu postpartum yang berada di wilayah kerja Puskesmas Gajah mada Tembilahan. Pengambilan sampel dalam penelitian ini mengunakan systematic random sampling dan responden dalam penelitian ini sebanyak 15 orang instrument dalam penelitian ini adalah Instrument kuesinoner untuk mengetahui tingkat kecemasaan dan kelelahan ibu pasca persalina. Dari hasil penelitian Sebagian besar ibu mengalami kelelahan signifikan (67%), yang dipengaruhi oleh faktor nyeri perineum, nyeri punggung, dan lamanya persalinan . Selain itu, lebih dari setengah responden (53,3%) mengalami kecemasan tinggi.